Cardiac involvement in Anderson–Fabry disease. The role of advanced echocardiography - Spinelli, Letizia; Bianco, Antonio; Riccio, Eleonora; Pisani, Antonio; Iaccarino, Guido (Frontiers in Cardiovascular Medicine, 2024)
Anderson-Fabry disease (AFD) is a lysosomal storage disorder, depending on defects in alpha galactosidase A activity, due to a mutation in the galactosidase alpha gene. Cardiovascular involvement represents the leading cause of death in AFD. Cardiac imaging plays a key role in the evaluation and management of AFD patients. Echocardiography is the first-line imaging modality for the identification of the typical features of AFD cardiomyopathy. Advanced echocardiography that allows assessment of myocardial deformation has provided insights into the cardiac functional status of AFD patients. The present review highlights the value and the perspectives of advanced ultrasound imaging in AFD.